DIVIDEND POLICY DETERMINANTS OF LISTED INDUSTRIAL GOODS FIRMS IN NIGERIA - Abdul-Khadir, Musa Ismail; Kolawole, Babajide; Aliyu, Abdullahi Awaisu (African Journal of Social and Behavioural Sciences, 2024)
This study investigates the determinants (using firm size, financial leverage and growth as proxies) of dividend policy (with dividend payout ratio as proxy) within listed industrial goods firms in Nigeria over a ten-year period from 2013 to 2022. Using a purposive sampling method, six firms were selected based on the availability of up-to-date financial statements within the study's scope. Secondary data extracted from annual financial reports and the Nigeria Exchange Group (NGX) formed the dataset for analysis. Employing an ex post facto research design, the study utilizes balanced panel data for both cross-sectional and time series analysis. Fixed effect panel regression was employed to estimate the relationship between the variables, The results shows that firm size had a significant positive relationship with dividend payout ratio; while both financial leverage (FLEV) and growth had nonsignificant negative relationship with dividend payout ratio of the firms. Based on these findings, it was recommended that; larger firms should capitalize on their size advantage to maintain or increase dividend payments, albeit caution is advised regarding leverage levels to prevent adverse effects on dividend distributions. Additionally, firms are urged to carefully assess the balance between reinvesting earnings for growth opportunities and distributing dividends to shareholders.